2019
DOI: 10.21608/resoncol.2019.7254.1072
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Treatment of Giant-Cell Tumor of Bone: a Single-Institutional Retrospective Study

Abstract: Background: Giant-cell tumor of bone (GCTB) is a locally aggressive tumor which metastasizes infrequently to the lungs. The standard treatment of GCTB was surgery until the approval of denosumab. Aim: To describe the outcome of treatment of this rare tumor and to determine factors that influence survival. Methods: Retrospective review of the medical records of GCTB patients treated at our institution. Collected data includes: clinicopathological data, treatment modalities and possible prognostic factors. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…All patients with histological confirmation of GCTB at our center were included in the study. We included some patients from a previous study that studied the prognosis of patients with GCTB on denosumab [ 6 ]. One of the limitations of the previous study is the smaller proportion of denosumab patients compared to non-denosumab patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients with histological confirmation of GCTB at our center were included in the study. We included some patients from a previous study that studied the prognosis of patients with GCTB on denosumab [ 6 ]. One of the limitations of the previous study is the smaller proportion of denosumab patients compared to non-denosumab patients.…”
Section: Methodsmentioning
confidence: 99%
“…Although recent studies have shown promising outcomes with denosumab, the long-term effects of denosumab have not been studied extensively. Additionally, studies analyzing the long-term effects of denosumab in the Middle Eastern region are limited by their small sample size [ 6 ]. Therefore, in this study, we compare the progression-free survival (PFS) of patients with GCTB who received denosumab versus those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…The abstract was presented at the European Society of Gynecological Oncology Congress, March 7-10 2024 in Barcelona, Spain, and published as abstract 391 in the International Journal of Gynecological Cancer ( 39 ).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…They are most often found at the ends of long bones and account for 5% of all primary bone tumors and 20% of all benign bone tumors [ 2 ]. The GCTB incidence is 1.3 per million persons per year based on a population study conducted in Sweden, which reported a female predominance with a female to male ratio of 1.3-1.5:1 [ 3 ]. GCTB emerge following skeletal maturity, with a peak incidence among those in their 20s and 30s [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…GCTB emerge following skeletal maturity, with a peak incidence among those in their 20s and 30s [ 4 ]. The clinical features include swelling, pain, and limitations in joint movement [ 3 ]. Around half of GCTB arise around the knee joint, either affecting the distal femur or proximal tibia [ 1 ].…”
Section: Introductionmentioning
confidence: 99%